Projet orchestre dans un collège REP+, à Toulouse : caractériser les difficultés déclarées par des professeurs chargés de l'enseignement musical - Lorraine Roubertie Soliman; Odile Tripier-Mondancin; Elisabeth Martinez; Nicole Bach
In some French schools/colleges, orchestra classes (2008) are specific devices: teachers from the French Ministry of Education, Conservatories and/or music schools are required to cooperate. The case of the Bellefontaine College orchestra classes within the Grand Mirail is part of this scheme. Few studies attempt to describe and understand the difficulties encountered by teachers in this type of project. However, the mission of the teachers attached to the Conservatory is not initially assigned to a captive school public, and is also in great difficulty. This contribution proposes to define, characterize and categorize the difficulties declared during interviews or testimonies of teachers involved in this system. Two main categories of difficulties emerge: those of teachers recruited by the conservatory, which seem to be related to intra- and inter-individual conflicts of values, and those of students.